Living by design : The partners of Pentagram - Crosby, Theo, author 394156; Fletcher, Alan, author 275943; Forbes, Colin, author 416700; Grange, Kenneth author 640294; Herron, Ron author 640295; Kurlansky, Mervyn author 640296; McConnell, John author 640297; Gorb, Peter, editor 243552 (London : L. Humphries ; New York : Whitney Library of Design, 1978)
Members of a successful design firm discuss the creation and principal uses of design motifs for products, informational items, environments, and conveying a distinctive personal identity.